Factors contributing to occupants’ comfort : A survey among occupants of academic buildings in a public university - Sharifah Noor Nazim, S.Y.; Ati Rosemary, M.A.; Muhammad Azzam, I. (2014)
Occupants’ comfort is always crucial in determining the quality of performance of an academic building and its facilities management. Factors such as thermal, acoustic, visual comfort and personal control of the building’s environmental condition generally contribute to the overall comfort level of its occupants. However, it is important to identify which of the factors contribute most to an occupant’s overall comfort. Therefore, this study investigates the relationship between comfort and its contributing factors by utilizing the Building Use Studies (BUS) questionnaire from the UK. The questionnaire was distributed to respondents from one of the earliest and prominent public university in Malaysia. The paper further investigates which type of personal control significantly influences the building occupants’ overall comfort. Analysis from 451 responses revealed that there is a significant correlation between overall comfort of the building’s occupants with two significant contributing factors which are; air condition (thermal comfort and air quality) and personal control. However, there is insufficient evidence that noise (acoustics) and lighting (visual) have significant correlation with a building occupants’ overall comfort level.